PENGUJIAN DAYA DUKUNG PERKERASAN JALAN DENGAN DYNAMIC CONE PENETROMETER (DCP) SEBAGAI STANDAR UNTUK EVALUASI PERKERASAN JALAN - Arie Syahruddin S. (Universitas Pasir Pengaraian, 2010)
Important factor in planning road maintenance and improvement include basic soil strength data, material properties, composition and thickness of existing pavement layers. Subgrade strength on the ground as the California Bearing Ratio (CBR), depending on conditions at the time of implementation and for ongoing service operation. Damage to roads that had been common, costly fact CBR data collection and maintenance efforts to slow constraints contributed to the severity of the condition of pavement is frequently traveled by traffic as people drive the economy. To obtain the above data, has introduced a tool Konus Dynamic Penetration (Dynamic Cone Penetrometer), which is a tool designed to test the strength of granular and subgrade layers of pavement quickly. Pavement layer is meant is the foundation of granular, soil stabilization, including the subgrade. Testing is done continuously to a depth of 80 cm and if necessary can be deepened with a connecting rod measuring up to 120 cm depth. In the last ten years, DCP has been widely used in obtaining data for pavement design CBR road so it's time DCP method can be used as test standards in Indonesia.